Pengaruh Pemberian Gymnastic Exercise Terhadap Keseimbangan Anak Usia 11-12 Tahun di SD N 03 Banjarharjo Kabupaten Karanganyar (Indonesian Journal for Physical Education and Sport, 2022)
Physical education learning Physical education learning at SD N 03 Banjarharjo was disrupted due to the covid-19 outbreak that hit the world, this made learning abolished which resulted in physical education learning being entirely done online. This makes the lack of balance and other activities. The purpose of this study was to determine the effect of giving gymnastics exercise on the balance of children aged 11 to 12 years at SD N 03 Banjarharjo. The method used in this research is experimental. experiment. The research method used to find the effect of certain treatments on others under controlled conditions. This study uses the One-Group Pretest Posttest DesignFrom the results of the study, it can be seen that based on the frequency distribution in the categorization of assessments, it can be seen that the data on balance skills skills of SDN 03 Banjarharjo students aged 11-12 years are 3 students (9%%) very good category, as many as 8 students (24.3%) good category, as many as 16 students (48.5%) in good enough category, as many as 6 students (18.2%) in poor category, and as many as 0 students (0%) in very poor category. From this study it can be concluded that there is a significant effect of gymnastics training on improving the balance of children aged 11-12 years at SDN 03 Banjarharjo, with t count 4.370 > t table 2.040 and sig 0.000 <0.05. The mean result of the pretest was 0.92 seconds and the posttest was 3.53 seconds. This shows that the average travel time for the balance skills test after treatment is longer, which means there is an increase in the balance skills of children aged 11-12 years at SDN 03 Banjarharjo. In this study, the product moment result was 0.617 which showed a positive effect. Suggestions for physical education teachers can use the results of this study as a guide to improve student balance at SD N 03 Banjarharjo.